RssB-mediated σS Activation is Regulated by a Two-Tier Mechanism via Phosphorylation and Adaptor Protein – IraD. Issue 3 (5th February 2021) - Wang, Zhihao; Zhao, Siyu; Li, Yanqing; Zhang, Kaining; Mo, Fei; Zhang, Jiye; Hou, Yajing; He, Langchong; Liu, Zhijun; Wang, Yawen; Xu, Yingqi; Wang, Hongliang; et al.
Graphical abstract: Highlights: Phosphorylation of RssB happens on the interface thus weakens the interaction σ S . IraD interacts with the RssB at higher affinity regardless of phosphorylation. A new two-tier mechanism for controlled proteolysis of σ S is proposed. RssB is fully activated during logarithmic growth, promoting σ S degradation. Phosphorylation on D58 partially switches the degradation off as the phosphorylation reduces RssB affinity for σ S . The binding of anti-adaptor protein IraD to RssB prevents any RssB- σ S interaction and shuts off σ S degradation completely. Abstract: Regulation of bacterial stress responding σ S is a sophisticated process and mediated by multiple interacting partners. Controlled proteolysis of σ S is regulated by RssB which maintains minimal level of σ S during exponential growth but then elevates σ S level while facing stresses. Bacteria developed different strategies to regulate activity of RssB, including phosphorylation of itself and production of anti-adaptors. However, the function of phosphorylation is controversial and the mechanism of anti-adaptors preventing RssB-σ S interaction remains elusive. Here, we demonstrated the impact of phosphorylation on the activity of RssB and built the RssB-σ S complex model. Importantly, we showed that the phosphorylation site - D58 is at the interface of RssB-σ S complex. Hence, mutation or phosphorylation of D58 would weaken the interaction of RssB with σ S . We found that the anti-adaptor protein IraD has higher affinity than σ S to RssB and its binding interface on RssB overlaps with that for σ S . And IraD-RssB complex is preferred over RssB-σ S in solution, regardless of the phosphorylation state of RssB. Our study suggests that RssB possesses a two-tier mechanism for regulating σ S . First, phosphorylation of RssB provides a moderate and reversible tempering of its activity, followed by a specific and robust inhibition via the anti-adaptor interaction.